Высокоэффективные катодные элементы для газоразрядных источников света - Sevastyanov, V. V.; Shutovsky, V. V. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
The use of cathode elements of an arc discharge activator made from a newly developed material — an alloy of iridium with rare-earth metals of the cerium group — has been proposed. Working samples of arc lamps have been manufactured and tested. The placement of the metal-alloy cathode has been optimized. Tests have shown that after 4,500 hours of operation, the ignition and luminous parameters of such lamps remained stable.